Effects of water quality on fish parasite biodiversity and physiological responses in the host fish Clarias gariepinus from a eutrophic lake subjected to acid mine drainage in South Africa - Latief, Lutfiyya; Gilbert, Beric M.; Avenant‐Oldewage, Annemariè (Integrated environmental assessment and management, 2024)
Elevated concentrations of contaminants have negative impacts on aquatic organisms and their parasites. Changes in parasite infections have been proposed as a technique for monitoring the health of aquatic ecosystems. Furthermore, alterations in physiological responses (biomarkers) of organisms have also been used to delineate ecosystem quality. Lake Heritage is situated along the Crocodile River in Muldersdrift, Gauteng, South Africa, and is subject to contamination by acid mine drainage. Clarias gariepinus is a well‐studied bioindicator species and host to numerous endoparasites and ectoparasites. The aims of this study were to delineate the health status of Lake Heritage through a multifaceted approach by comparing the water quality, biomarker responses, and parasite biodiversity of C. gariepinus, compared to unexposed laboratory‐reared fish. Physical and chemical water quality parameters were determined using a hand‐held probe, test kits, and element analysis with inductively coupled plasma‐mass spectrometry. Biomarker responses in the gill, liver, and muscle tissues from C. gariepinus were assessed for total protein, metallothioneins, superoxide dismutase (SOD), and reduced glutathione (GSH) concentrations and activities of acetylcholinesterase and catalase. Results for water quality variables showed higher pH, nitrate, hardness, and copper levels compared with the South African Target Water Quality Guidelines. Catalase activity and concentrations of SOD and reduced GSH showed a response in C. gariepinus to the water quality. Ectoparasites had lower prevalence and mean intensity than endoparasites. However, there were no differences in the physiological responses between infected and uninfected hosts. The study shows that the eutrophic conditions in Lake Heritage cause biomarker responses in the host when compared to host fish in laboratory conditions. Integr Environ Assess Manag 2024;20:1539–1553. © 2023 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points The water quality in this river is impacted by acid mine drainage (AMD), sporadic treatment of AMD, point‐source pollution, and runoff. Inhibition of acetylcholine esterase activity in Clarias gariepinus implies that organophosphate and carbamates are also entering the system, and the lake is eutrophic. Ectoparasite infection intensity, number, and diversity are reduced, while endoparasite numbers and diversity are higher. Water quality has a greater impact on the physiological response of the host, compared to the effect caused by the endoparasites or ectoparasites.